PROCESSO DE RECRUTAMENTO PARA O SERVIÇO MILITAR: UMA ABORDAGEM SISTÊMICA PARA A EXCELÊNCIA NO SISTEMA DE GESTÃO. - Encarnação Filho, Orlando Pessanha da (2003)
The objective of this thesis is measure the cultural, social, military, and technical aspects of nature that characterize the mandatory military service from the recruitment and selection of the conscritos incorporated in the caserne from the 2ª Circumscription of Military Service, Niterói, Rio de Janeiro in the year of 2003. Such research resulted in recommendations that they contribute with the gestores of military institutions in the improvement from the management of the recruitment and selection of conscritos. The facts collected through of qualitative research of characteristic exploratory serve to a reflection about the possibility of take advantage of better the human resorts that incorporate the Organizations military of the Army in the city of the rio de janeiro. The interviews carried out pretend the obtaining of information for the perfection of the work where the recruits are applied.